2015
DOI: 10.1371/journal.pone.0132969
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Characterization of the Mung Bean Transcriptome and Transcriptomic Analysis of Adventitious Rooting in Seedlings Using RNA-Seq

Abstract: Adventitious rooting is the most important mechanism underlying vegetative propagation and an important strategy for plant propagation under environmental stress. The present study was conducted to obtain transcriptomic data and examine gene expression using RNA-Seq and bioinformatics analysis, thereby providing a foundation for understanding the molecular mechanisms controlling adventitious rooting. Three cDNA libraries constructed from mRNA samples from mung bean hypocotyls during adventitious rooting were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…‘M.26’ dwarfing apple rootstocks are widely used because they offer size control and other beneficial traits to the grafted scions. Although the development of dwarfing apple rootstocks is a major pursuit of the global apple industry, apple rootstock breeding programs in China have not been well established (Li et al ). Apple scions can be grafted onto desirable rootstocks to acquire the ability to adapt to certain soil conditions or resistance to soilborne pests and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…‘M.26’ dwarfing apple rootstocks are widely used because they offer size control and other beneficial traits to the grafted scions. Although the development of dwarfing apple rootstocks is a major pursuit of the global apple industry, apple rootstock breeding programs in China have not been well established (Li et al ). Apple scions can be grafted onto desirable rootstocks to acquire the ability to adapt to certain soil conditions or resistance to soilborne pests and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some other genes and proteins have been studied to relate to the vegetative propagation, like RP [47], HSP [48], and histone [49,50]. While very few studies have been demonstrated to investigate their functions and associations in the SE of Eucalyptus, our results indicate that the dysregulation of these genes or the known pathways like metabolisms involved by these genes might be related to the SE of Eucalyptus.…”
Section: Snps and Indelsmentioning
confidence: 72%
“…The functions of cell wall related genes need future experiments to be explored. Furthermore, RP [48], HSP [49], and histone [50,51] have been reported to function in the vegetative propagation in plants. While very few studies have been demonstrated to investigate their functions and associations in the SE of Eucalyptus, our results indicate that the dysregulation of these genes and pathways like metabolisms involved by these genes might play important roles in the SE of Eucalyptus.…”
Section: Discussionmentioning
confidence: 99%